2005
DOI: 10.1111/j.1460-9592.2005.01777.x
|View full text |Cite
|
Sign up to set email alerts
|

Propofol anesthesia in spontaneously breathing children undergoing magnetic resonance imaging: comparison of two propofol emulsions

Abstract: Propofol-based short-term anesthesia was well suited for anesthesia during MRI procedures in the studied pediatric patients. There were no clinically relevant differences between the two propofol formulations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 38 publications
2
9
0
Order By: Relevance
“…This unusually high incidence of upper airway obstruction may have been due to our use of relatively low infusion rates of propofol. While considerably higher propofol infusion rates up to 250 mcg·kg −1 ·min −1 have been successfully used for MRI , the lower doses of propofol used in our study are consistent with infusion rates reported in the literature , particularly when accompanied by premedication . Indeed prior to using the new 3T MRI, our standard propofol sedation regimen for the 1.5T MRI, preceded by midazolam premedication, had been highly successful.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…This unusually high incidence of upper airway obstruction may have been due to our use of relatively low infusion rates of propofol. While considerably higher propofol infusion rates up to 250 mcg·kg −1 ·min −1 have been successfully used for MRI , the lower doses of propofol used in our study are consistent with infusion rates reported in the literature , particularly when accompanied by premedication . Indeed prior to using the new 3T MRI, our standard propofol sedation regimen for the 1.5T MRI, preceded by midazolam premedication, had been highly successful.…”
Section: Discussionsupporting
confidence: 85%
“…The loading doses of dexmedetomidine and induction doses and maintenance infusion rates for propofol used in this study have been reported as safe and effective dosing regimens in the literature for MRI . Continuous infusion rates for propofol were lower than a number of reported studies yet similar to studies where premedication was used prior to procedural sedation . We used a modified (in reverse order) Children's Hospital of Wisconsin Sedation Scale to assess sedation levels (0 Inadequate: anxious, agitated, or in pain; 1 Minimal: spontaneously awake without stimulus; 2 Drowsy: eyes open or closed, but easily arouses to consciousness with verbal stimulus; 3 Moderate‐deep: arouses to consciousness with moderate tactile or loud verbal stimulus; 4 Deep: arouses slowly to consciousness with sustained painful stimulus; 5 Deeper: arouses, but not to consciousness, with painful stimulus; 6 Anesthesia: unresponsive to painful stimulus) .…”
Section: Methodsmentioning
confidence: 97%
“…In over 96% of all patients, sedation was rated ‘ideal’, and in only 2% of the cases was sedation so poor that the procedure could not be performed. These rates compare favorably to previously reported smaller studies involving pentobarbital (1–5) and propofol (8,9,14,17) for imaging‐related sedation. Only one prior study, involving 30 patients per group, directly compared i.v.…”
Section: Discussionsupporting
confidence: 84%
“…Deep sedation is typically induced with a bolus dose of 1-3 mg/kg and 0.5-1 mg/kg supplementation every 1-2 minutes [61]. Higher dosing is often required for younger pediatric patients because of their higher volume of distribution, shorter elimination half-life, and higher plasma clearance [62]. A single dose or intermittent bolus doses of propofol may be suitable for brief procedures ( < 30 minutes) [63], but continuous infusion of 2-5 mg/kg/hr rather than intermittent administration is recommended for longer procedures [64] in children undergoing MRI.…”
Section: ) Propofolmentioning
confidence: 99%